Systemic PEGylated TRAIL treatment ameliorates liver cirrhosis in rats by eliminating activated hepatic stellate cells. Issue 1 (3rd March 2016) - Oh, Yumin; Park, Ogyi; Swierczewska, Magdalena; Hamilton, James P.; Park, Jong‐Sung; Kim, Tae Hyung; Lim, Sung‐Mook; Eom, Hana; Jo, Dong Gyu; Lee, Choong‐Eun; Kechrid, Raouf; Mastorakos, Panagiotis; et al.
Abstract : Liver fibrosis is a common outcome of chronic liver disease that leads to liver cirrhosis and hepatocellular carcinoma. No US Food and Drug Administration–approved targeted antifibrotic therapy exists. Activated hepatic stellate cells (aHSCs) are the major cell types responsible for liver fibrosis; therefore, eradication of aHSCs, while preserving quiescent HSCs and other normal cells, is a logical strategy to stop and/or reverse liver fibrogenesis/fibrosis. However, there are no effective approaches to specifically deplete aHSCs during fibrosis without systemic toxicity. aHSCs are associated with elevated expression of death receptors and become sensitive to tumor necrosis factor–related apoptosis‐inducing ligand (TRAIL)‐induced cell death. Treatment with recombinant TRAIL could be a potential strategy to ameliorate liver fibrosis; however, the therapeutic application of recombinant TRAIL is halted due to its very short half‐life. To overcome this problem, we previously generated PEGylated TRAIL (TRAILPEG ) that has a much longer half‐life in rodents than native‐type TRAIL. In this study, we demonstrate that intravenous TRAILPEG has a markedly extended half‐life over native‐type TRAIL in nonhuman primates and has no toxicity in primary human hepatocytes. Intravenous injection of TRAILPEG directly induces apoptosis of aHSCs in vivo and ameliorates carbon tetrachloride‐induced fibrosis/cirrhosis in rats by simultaneously down‐regulating multiple key fibrotic markers that are associated with aHSCs. Conclusion : TRAIL‐based therapies could serve as new therapeutics for liver fibrosis/cirrhosis and possibly other fibrotic diseases. (Hepatology 2016;64:209–223)